Contribution of Filopodia to Cell Migration: A Mechanical Link between Protrusion and Contraction. (20th June 2010) - Xue, Fei; Janzen, Deanna M.; Knecht, David A.
Abstract : Numerous F-actin containing structures are involved in regulating protrusion of membrane at the leading edge of motile cells. We have investigated the structure and dynamics of filopodia as they relate to events at the leading edge and the function of the trailing actin networks. We have found that although filopodia contain parallel bundles of actin, they contain a surprisingly nonuniform spatial and temporal distribution of actin binding proteins. Along the length of the actin filaments in a single filopodium, the most distal portion contains primarily T-plastin, while the proximal portion is primarily bound byα -actinin and coronin. Some filopodia are stationary, but lateral filopodia move with respect to the leading edge. They appear to form a mechanical link between the actin polymerization network at the front of the cell and the myosin motor activity in the cell body. The direction of lateral filopodial movement is associated with the direction of cell migration. When lateral filopodia initiate from and move toward only one side of a cell, the cell will turn opposite to the direction of filopodial flow. Therefore, this filopodia-myosin II system allows actin polymerization driven protrusion forces and myosin II mediated contractile force to be mechanically coordinated.